Synthesis of a 2-N, N-dibenzylamino glucopyranosyl trichloroacetimidate glycosyl donor and evaluation of its utility in stereoselective glycosylation. (February 2016) - Ali, Stacy P.; Jalsa, Nigel Kevin
Highlights: The 2-N, N-dibenzylamino glucopyranosyl trichloroacetimidate donor was synthesized. Extensive glycosylation studies were conducted with the dibenzylamino donor. Exclusive β-stereoselectivity was obtained in moderate to good yields. Graphical abstract: Abstract: The 2-N, N-dibenzylamino glucopyranosyl trichloroacetimidate donor was synthesized and an extensive investigation of its glycosyl donor properties was conducted. Coupling studies incorporated a variety of glycosyl promoters and a range of acceptor alcohols representing different reactivities and protecting group patterns. Various reaction temperatures, solvents and glycosylation protocols were also examined. Exclusive β-stereoselectivity was obtained in moderate to good yields with eight novel glycosides being produced, by probable neighbouring group participation via the formation of an aziridinium ion intermediate. Plausible reaction mechanisms were proposed based on the results obtained.